Does simulation training result in improved on-call outcomes among newly appointed radiology registrars?. Issue 5 (May 2023) - Butt, M.; Skarparis, Y.; Self, A.
Abstract : Aim: To quantify the impact of a marked increase in radiology trainee numbers and the compensatory introduction of formal simulation on-call training by investigating the discrepancy rates among on-call radiologists in training before and after the introduction of structured simulation training. Materials and methods: The first 100 cases reported by a cohort of Specialty Trainee Year 2 doctors (ST2), having commenced on-call reporting, were analysed. This included registrars working in two major tertiary centres. Two groups of registrars were compared directly: those who undertook the simulation training and those who did not. Discrepancies were divided by severity into minor, moderate, and major categories. The criteria for each category were based on previously published literature. Results: Twelve registrars from 2017 were compared with 12 from previous years (two in 2013, four in 2014, and six in 2015); 2, 320 cases were analysed. There was a statistically significant reduction in the total number of discrepancies ( p =0.01) made by registrars who underwent simulation training. A similar improvement was observed in the number of major discrepancies; however, this was not statistically significant. Conclusion: The present study shows that simulation training successfully increases competency in on-call work. Despite doubling the number of doctors in training, discrepancy rates did not worsen and in fact improved.